(untitled) (Chicago, 2001)
Leading writers and poets, such as LeAnne Howe, Julian Lang, Caren Wallace, and Sulieman Allen, contribute to this collection of stories that captures the Native American spirit, humor, and reality. Hozho, the Navajo word meaning walking in beauty, explores such themes as invisibility, transcendence, the oral tradition, and the role of humor and irony in Indian culture.
Keywords: American fiction,Short stories, american,Indians of North America,Truyện ngắn Mỹ; Indian authors